Application of "smart" multifunctional nanoprobes in tumor diagnosis and treatment. Issue 19 (19th April 2022) - Xuan, Yang; Gao, Yating; Guan, Meng; Zhang, Shubiao
Abstract : Illustration of the preparations, applications and mechanisms of two kinds of "smart" multifunctional nanoprobes: "Off–On" nanoprobes and "Charge-Reversal" nanoprobes. Abstract : Cancer is one of the major diseases that pose a threat to human health and life, especially because it is difficult to diagnose and cure, and recurs easily. In recent years, the development of nanotechnology has provided researchers with new tools for cancer treatment. In particular, nanoprobes that facilitate integrated diagnosis and treatment, high-resolution imaging, and accurate tumor targeting provide new avenues for the early detection and treatment of cancer. This review focuses on the preparations and applications of two kinds of "smart" multifunctional nanoprobes: "Off–On" nanoprobes and "Charge-Reversal" nanoprobes. This review also briefly discusses their mechanisms of action, as they could provide new ideas for the further development of this field.